Comprehensive Testing of Positionally Cloned Asthma Genes in Two Populations - Craig P. Hersh; Benjamin A. Raby; Manuel E. Soto-Quirós; Amy Murphy; Lydiana Ávila; Jessica Lasky‐Su; Jody Sylvia; Barbara J. Klanderman; Christoph Lange; Scott T. Weiss; Juan C. Celedón (2007)
Replication of gene-disease associations has become a requirement in complex trait genetics.